Problem solving skill through think pair share model with murder approach viewed from learning interest of tenth grade students - Millah, Najichatul; Waluya, St. Budi; Walid, Walid (Unnes Journal of Mathematics Education, 2018)
This research focuses on problem-solving capability through Think Pair Share model with MURDER approach viewed from learning interest of the students. TPS learning with MURDER approach was conducted through three phases of TPS namely Think, Pair, and Share. This research aims to testthe completeness of problem-solving through TPS model with MURDER approachand to describe the problem-solving capability through TPS model with MURDER approach viewed from students’ learning interest.This research usedmixed methods with concurrent embedded design. The samples of this research weretenth-grade students of AP (experimental class) andtenth grade TP A (control class) of State Vocational High School 2 Rembang who were chosen through random sampling technique. The quantitative data collection technique used test, while qualitative data collection used triangulation technique. Sample selection on qualitative research used purposive sampling technique. The qualitative datawere analyzed by usingnormality, homogeneity, equality of two means, t, and z tests. Qualitative data were analyzed by using data validation test, data reduction, data presentation, and verification andconclusion drawing. The results of the research showedthat the (1) problem-solving capabilities of the students through TPS model with MURDER approach has reached individual and classical completeness, (2) the problem solving capabilities of the students through TPS model with MURDER approach was better than the problem solving capabilities of the studentsthrough expository learning model, (3) students with high learning interestcould fulfill all problem solving capability indicators, (4) students with moderate learning interestcould fulfill fourproblem solving capability indicatorsbut they tend to be lessthorough, and (5) students with low learning interestwere less able to fulfill appropriate strategies application indicators to solve the problem.